Penerapan Media Tusuk Sate untuk Meningkatkan Keterampilan Menyimak (Maharah Istima’) pada Mata Pelajaran Bahasa Arab - Siti Fauziah Rahmani Rasyid; Ani Siti Anisah; Iis Komariah (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
The purpose of this study was to determine the effectiveness of the application of skewer media to improve listening skills (maharah istima') in Arabic language subjects with a sample of 27 people. This study was conducted by distributing questionnaires and completing tests in the form of questions related to the material taught using skewer media. In addition to the technique of distributing questionnaires and test questions, this study used observation, interview, and documentation techniques. This study used a quantitative research approach, the type of research used was experimental research. Experimental research is a research method used to influence certain actions or treatments carried out for certain conditions. This study involved 14 students out of a total of 27 students in class VA MIN 2 Garut. Listening skill data was collected by a listening skill test in the form of a description. The skewer media is one of the educational game techniques used to teach Arabic, especially to improve students' listening and listening skills, as well as their vocabulary. The educational game method helps students improve their vocabulary and classify different types of words. This game is very important for teaching classification and recognition. Using skewers as a medium, students can understand various types of sentences, sentence punctuation, and other components. The results indicate that using skewers to improve students' listening skills in class VA MIN 2 in Garut is quite effective. The results are based on a comparison of the average scores of students' learning tests using a t-test. This is supported by the proportion of students' classical mastery and an analysis of their post-test averages.